Urochloa brizantha and Amazonian Dark Earths reshape soil microbiota without affecting tree growth in degraded Central Amazon Oxisols - Anderson Santos de Freitas; Rogério Eiji Hanada; Aleksander Westphal Muniz; Siu Mui Tsai (Soil Ecology Letters, 2026)
Amazonian Dark Earths (ADE) and Urochloa brizantha conditioned soil (CS) did not improve early tree growth. Combination CS+ADE reduced Gram-positive bacteria and Herbaspirillum by 3-fold. Microbial networks were stronger in Cecropia and Acacia with the combination CS+ADE. β-glucosidase activity declined 70% in Acacia under CS+ADE. Native Oxisol microbiota showed resilience to ADE-based treatments. Amazonian Dark Earths (ADE) are fertile anthropogenic soils rich in organic matter and microbial diversity, offering potential for restoring degraded tropical soils. We tested the combined effects of ADE (2% w/w) and Urochloa brizantha conditioned soil (CS 20%) on soil microbial communities and early growth of four tree species ( Cecropia pachystachya, Schizolobium amazonicum, Handroanthus avellanedae, Acacia mangium ) in a pasture-degraded Oxisol. Plant performance, soil enzyme activity, prokaryotic community structure (16S rRNA sequencing), predicted functions, and co-occurrence networks were evaluated. Neither ADE nor U. brizantha , alone or combined, significantly improved tree growth or microbial alpha diversity ( p < 0.05). However, the combination CS+ADE shifted microbial composition, reducing by 3-fold the abundance of several aerobic Gram-positive taxa ( Actinophytocola, Lysinibacillus, Rubrobacter ) and nitrogen-fixers ( Herbaspirillum ). Network analyses showed treatment-specific connectivity changes, especially in Cecropia and Acacia, where CS+ADE increased both positive and negative microbial associations. Functional prediction and enzyme assays revealed a largely stable functional core, except for a 70% decline in β-glucosidase activity in Acacia under CS+ADE, indicating altered carbon cycling. Overall, while microbial networks responded strongly, limited ADE input and the stability of native microbiota constrained plant and functional benefits, underscoring the importance of application strategies in restoration.